Evaluation of In-Vitro Anticancer Activity of Hibiscus Rosa Sinensis against HeLa cell Line - P. Sampath Kumar (Journal of Global Pharma Technology, 2018)
The antifungal activity of Hibiscus rosa sinensis was evaluated against the following pathogenic fungi such as Candida albicans, Aspergillus niger, Trichoderma viride and  Rhizopus microsporus. The acetone extract of Hibiscus rosa sinensis flower showed little antifungal activity.  The acetone extract of Hibiscus rosa sinensis flower showed higher activity against HeLa cell line using MTT assay. The results obtained from the study revealed that Hibiscus rosa sinensis flower  Possess anticancer  activity against HeLa cell line using MTT assay.